Complete Genome Sequence of the Endophytic Bacterium Bacillus cereus PgBE311, Isolated from Panax ginseng - Hong, Chi Eun (Microbiol Resour Announc, 2018)
Bacillus cereus PgBE311, isolated from the root tissue of a 5-year-old Panax ginseng plant, showed activities against the fungal pathogens Cylindrocarpon destructans and Botrytis cinerea. Here, we report the genome sequence of B. cereus PgBE311. The bacterium contains antibiotic-related gene clusters and has the potential to stimulate plant growth.